Error Analysis on the Students Pronunciation of Affricates Sounds at SMA Negeri 10 Medan - Rambe, Nana Ronawan (LP2M IAIN Ambon, 2019)
Abstract This article deal with error analysis on the students’ pronunciation of affricates sounds. The method of research applied was descriptive quantitative method. It was applied to find and to analyze error analysis on the students’ pronunciation of affricates sounds. The population of this research was the first year students of SMA NEGERI 10 MEDAN at Jl.Tilak Medan. There were 47 students in parallel classes and all of them were taken as the sample. The instrument of the research was administrated test. The test was teacher made test. There were 20 items were given to the students. The test results were analyzed by finding out the percentages of students’ error in pronunciation affricates sounds. The total correct answer of the test were 437 or 9,340% and incorrect answer were 407 or 8,659 % .There were 3 causes of errors analysis on the students’ pronunciation of affricates sounds, they were intralingual, interlingual, and carelessness.There were 44 or 10, 09% for intralingual errors, 98 or 22,47% for interlingual errors and 295 or 67,50 % for carelessness errors. Keywords:Affricates, Eror,Causes. Abstrak Artikel ini membahas analisis kesalahan pelafalan bunyi afrikat pada siswa. Metode penelitian yang digunakan adalah metode deskriptif kuantitatif. Itu diterapkan untuk menemukan dan menganalisis analisis kesalahan pada pelafalan bunyi afrikat siswa. Populasi penelitian ini adalah siswa tahun pertama SMA Negeri 10 Medan di jalan.Tilak Medan yang terdiri dari 47 siswa di kelas paralel dan semuanya diambil sebagai sampel. Instrumen penelitian adalah tes administrasi. Tes adalah tes yang dibuat guru. Ada 20 item yang diberikan kepada siswa. Kemudian jawaban dianalisis dengan mencari tahu persentase kesalahan siswa dalam pelafalan melafalkan bunyi untuk menunjukkan bahwa total jawaban yang benar dari tes adalah 437 atau persentase 9,340% dan jawaban yang salah adalah 407 atau persentase 8,659% ada 3 penyebab analisis kesalahan pada pengucapan bunyi afrikat siswa, itu adalah intralingual, interlingual, dan kecerobohan. Untuk kesalahan intralingual adalah 44 atau 10, 09%, untuk kesalahan interlingual adalah 98 atau 22,47% dan untuk kesalahan kecerobohan adalah 295 atau 67,50%. Kata Kunci: Afrikat, Kesalahan, Penyebab.